Design and simulation of low power consumption polymeric based MMI thermo-optic switch - Mohd Ridzuan, Noridah (2013)
In optical communication system, optical cross connect devices particularly an optical switch has become the main attraction for research due to its ability to route optical data signals without the need for conversion to electrical signals. Thus, it is important to develop optical devices such as optical switch with low power consumption and crosstalk for Wavelength Division Multiplexing (WDM) lightwave communication system. This project aims towards the design and simulation work of a polymeric based thermo-optic switch using Multimode Interference (MMI) structure to achieve low switching power capability and reduce crosstalk figure. The optical switch is designed on the 2x2 MMI cross coupler architecture of optical switch based on the general interference mechanism. Light propagation and thermal distribution through the optical switch is modeled using Finite Difference Beam Propagation Method (FD-BPM). Photosensitive SU-8 epoxy polymeric based waveguide material at core layers with PMGI at upper and lower cladding layer were chosen due to its low thermal conductivity and high thermo-optic coefficient. Further analysis has been performed by exploring the effect of heater‟s structure and its placement in order to reduce switching power. It is observed that by applying well-designed of heater‟s structure and suitable placement of heater, low power consumption as low as 9.05 mW with crosstalk level of -36.52 dB can be achieved.